Case report: A successful second autologous hematopoietic stem cell transplantation in refractory systemic sclerosis, with positive effect on skin involvement, pulmonary function and microcirculation - Haverkort, D.A.; Kersten, B.E.; van Rhenen, A.; van der Velden, W.J.F.M.; Vonk, M.C. (Frontiers in Immunology, 2022)
Background: Systemic sclerosis (SSc) is a complex autoimmune disease characterized by inflammation, vasculopathy and fibrosis of the skin and internal organs. Treatment with autologous hematopoietic cell transplantation (HCT) for progressive SSc has improved overall and event-free survival rates significantly, but unfortunately disease progression after HCT is seen in a subset of patients. Data on the efficacy and safety of second HCT is scarce. Case: We present a patient with diffuse cutaneous SSc and associated interstitial lung disease (ILD) who successfully underwent a second HCT for progressive disease five years after a first HCT. We describe changes in skin involvement and pulmonary involvement as well as the changes observed in sequential nailfold microcapillaroscopy (NCM), performed from first presentation up to this moment. Conclusion: This case adds to the current limited literature on efficacy and safety of a second HCT in SSc refractory cases. Furthermore it outlines the potential of HCT on amelioration of microvasculopathy in SSc.